2013
DOI: 10.1111/aji.12104
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Carcinoma Cells Stimulate the Angiogenesis through TSLP Promoting Growth and Activation of Vascular Endothelial Cells

Abstract: This study has demonstrated that TSLP secreted by cervical carcinomas cells is involved in the angiogenesis of cervical cancer in a paracrine manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 41 publications
3
52
0
Order By: Relevance
“…A fundamental step in the transition of tumors from dormant to malignant state is followed by the potential for metastasis. Inhibiting the angiogenesis and metastasis of human cervical cancer cells could serve as an effective strategy against cervical cancer progression (Xie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental step in the transition of tumors from dormant to malignant state is followed by the potential for metastasis. Inhibiting the angiogenesis and metastasis of human cervical cancer cells could serve as an effective strategy against cervical cancer progression (Xie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous cytokines, including VEGF, regulate the functions of vascular endothelial cells (32)(33)(34). Our previous study demonstrated that cervical cancer cells stimulate angiogenesis of vascular endothelial cells by secreting TSLP (18).…”
Section: Discussionmentioning
confidence: 99%
“…The TSLP receptor (TSLPR) is a typical heterodimeric cytokine receptor consisting of a TSLP binding subunit (TSLPRα) and the α-subunit of the IL-7 receptor (IL-7Rα) (16,17). Our previous study demonstrated that TSLP secreted by cervical cancer cells promotes angiogenesis (18). In addition, an increased level of TSLP in cancer lesions, mediated by hypoxia, was a regulator of the progression of cervical cancer, and functioned by recruiting and enabling tumor-associated eosinophils (EOS) to promote the growth of the cervical cancer cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that H. pylori infection directly induced TSLP production from human gastric epithelial cells [12,24]. Recent research showed that TSLP could be involved in the progression of breast, lung, pancreatic, and cervical cancers; however, the regulatory mechanisms of TSLP in these cancers are not well defined [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%